2020
DOI: 10.1001/jamapediatrics.2019.5209
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Antigen Shedding in the Breast Milk of Mothers From a Region With Endemic Malaria

Abstract: Dr Verhasselt had full access to all of the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis. Drs Verhasselt and Egwang contributed equally as senior authors. Concept and design: Verhasselt, Egwang. Acquisition, analysis, or interpretation of data: All authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…While anaemia decreases significantly. This might be due to the stimulation of antimalarial immune defenses by malaria antigen in breast milk which reduces malaria risk in infants attributable to breastfeeding [ 30 ]. As children are weaned, they are vulnerable to malaria as they have lost maternal immunity and are yet to develop self-immunity against infection [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…While anaemia decreases significantly. This might be due to the stimulation of antimalarial immune defenses by malaria antigen in breast milk which reduces malaria risk in infants attributable to breastfeeding [ 30 ]. As children are weaned, they are vulnerable to malaria as they have lost maternal immunity and are yet to develop self-immunity against infection [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…12 This concept is supported by a recent report of Plasmodium falciparum blood stage antigens in human breast milk. 13 In this report, we present preliminary evidence that intranasal administration of recombinant SE36 antigen to lactating mice results in the appearance of the antigen in breast milk and that pups borne of immunologically naïve mice not exposed to SE36 develop IgG anti-SE36 antibodies following breastfeeding by SE36-exposed foster mothers. SE36 is a promising malaria vaccine candidate derived from P. falciparum serine rich antigen 5.…”
Section: Methods Results and Discussionmentioning
confidence: 80%
“…Malaria blood-stage antigens have been demonstrated in human breast milk, but the mechanism of antigen transport remains unknown. 13 The public health significance of malaria antigen shedding in breast milk remains to be investigated in prospective studies of mother-infant pairs. Vaccination against killer diseases by infants nursing on lactating mothers shedding vaccines in milk would be transformative for infant vaccinology if validated and would boost breastfeeding promotions.…”
Section: Methods Results and Discussionmentioning
confidence: 99%
“…Neonates mount an efficient cytotoxic immune response to a viral dose 10,000 times lower than an adult, while higher doses are unable to activate an appropriate immune response 9 . The levels of P. falciparum antigen histidine-rich protein 2 and hepatitis B e antigen are 10-100-fold lower, and hepatitis B surface antigens are 30,000 times lower in human milk than in serum 7 , 10 . These low levels may be an important cue for the developing immune system of the neonate.…”
Section: How Can Antigen In Breast Milk Effectively Vaccinate Children?mentioning
confidence: 95%
“…More recently, a study demonstrated development of mucosal immunity to SARS-CoV-2 in newborns breastfed by SARS-CoV-2 infected mothers, without any sign of infection in the offspring 5 . Parasitic antigens such as from Schistosoma mansoni 6 and Plasmodium falciparum 7 are also present in breast milk of infected women. While currently there is no data from birth cohorts on the possible immunization of children exposed to parasite antigen through breast milk, one study demonstrated better defence against S. mansoni in young adult mice when they had been nursed by S. mansoni -infected mothers 8 .…”
Section: Evidence Of Infant Vaccination Through Exposure To Pathogen ...mentioning
confidence: 99%